Targeting Peroxisome Proliferator-Activated Receptor-α (PPAR- α) to reduce paclitaxel-induced peripheral neuropathy - Caillaud, Martial; Patel, Nipa H.; White, Alyssa; Wood, Mackinsey; Contreras, Katherine M.; Toma, Wisam; Alkhlaif, Yasmin; Roberts, Jane L.; Tran, Tammy H.; Jackson, Asti B.; Poklis, Justin; Gewirtz, David A.; et al. (Brain, behavior, and immunity, 2021)
[Display omitted] •Already known: Paclitaxel, a widely used anti-cancer drug, is frequently associated with prolonged and severe peripheral neuropathies, with neuroinflammation.•This study adds: PIPN induce PPAR-⍺ expression decrease in DRG associated with an increase in neuroinflammation.•This study adds: The use of PPAR-⍺ agonists (Fibrates) significantly reduces signs of PIPN.•This study adds: Reduction of PIPN hypersensitivity by Fibrates, involves regulation of PPAR-⍺ and decrease neuroinflammation in DRG.•The clinical significance: Fibrates could be the subject of pharmacological repurposing for the treatment of PIPN. Paclitaxel, a widely used anti-cancer drug, is frequently associated with prolonged and severe peripheral neuropathies (PIPN), associated with neuroinflammation. Currently, PIPN effective treatments are lacking. Peroxisome Proliferator-Activated Receptor-α (PPAR-⍺) can modulate inflammatory responses. Thus, the use of PPAR-⍺ agonists, such as fibrates (fenofibrate and choline-fenofibrate), currently used in dyslipidemia treatment, could represent an interesting therapeutic approach in PIPN. Our studies tested the efficacy of fenofibrate (150 mg/kg, daily, i.p.) and choline fenofibrate (60 mg/kg daily, p.o.) in reversing and preventing the development of PIPN (paclitaxel: 8 mg/kg, i.p., every other day for 4 days) in male and female C57BL/6J mice. Mechanical and cold hypersensitivity, conditioned place preference, sensory nerve action potential (SNAP), as well as the expression of PPAR-⍺, TNF-⍺, IL-1β and IL-6 mRNA were evaluated. While fenofibrate treatment partially reversed and prevented the development of mechanical hypersensitivity, this was completely reversed and prevented by choline-fenofibrate. Both fibrates were able to completely reverse and prevent cold hypersensitivity induced by paclitaxel. The reduction of SNAP amplitude induced by paclitaxel was also reversed by both fenofibrate and choline-fenofibrate. Our results indicate that suppression of paclitaxel-induced hypersensitivity by fibrates involves the regulation of PPAR-⍺ expression and decrease neuroinflammation in DRG. Finally, the co-treatment of Paclitaxel and fenofibric acid (fibrates active metabolite) was tested on different cancer cell lines, no decrease in the antitumoral effect of paclitaxel was observed. Taken together, our results show for the first time the therapeutic potential (prevention and reversal) of fibrates in PIPN and opens to a potential pharmacological repurposing of these drugs.